Occupational Structure of Tribal Population in South-East Rajasthan: A Geographical Analysis - Patidar, Hemant; Singh, M. B. (National Geographical Journal of India, 2022)
The tribes are socio-economically very backward because they have been in lesser touch to the contemporary technologically modern society of our time. Besides, their attachment to primitive economy and socio-cultural traditions has kept them aloof from their wholesome development. Despite concerted efforts, made by central as well as state government, a greater share of tribal population is engaged in traditional primitive economy. This paper aims to ascertain the proportion of tribal share in secondary and tertiary economic activities and their specialization pattern in each district in respect to the region. The data, collected from State Primary Abstract and Special Tables on STs for the three successive Censuses- 1981, 1991 and 2001, have been used for this purpose. To obtain the proportion of workers in secondary and tertiary activities, data have been computed into percentage form and in addition the Location Quotient method has been applied to measure specialization pattern of each district in particular economic activity. The analysis portrays that the tribal population in South-East Rajasthan is very much engaged in primitive economic activities such as agriculture, plantation, forestry, mining, etc. Though the proportion of tribal workforce in secondary and tertiary activities, with government and non-government interference, has experienced slight increase but still it is very meager. In order to uplift the economic level of this subgroup of our society, a strong policy initiative has to be undertaken.